2013
DOI: 10.1186/1471-2229-13-187
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional promoters in seed development and related hormone/stress responses

Abstract: BackgroundBidirectional promoters are common in genomes but under-studied experimentally, particularly in plants. We describe a targeted identification and selection of a subset of putative bidirectional promoters to identify genes involved in seed development and to investigate possible coordinated responses of gene pairs to conditions important in seed maturation such as desiccation and ABA-regulation.ResultsWe combined a search for 100–600 bp intergenic regions in the Arabidopsis genome with a cis-element b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 81 publications
1
13
0
Order By: Relevance
“…S5A) (23). Our initial approach was to assign only the nearest TSS as a target of the peak, but we expanded our analysis to include all TSS within 1 kb of the peak, thus allowing more than one target per peak and the inclusion of bidirectional promoters (51,52). This inclusive target list identified 2,327 TSS within 1 kb of the peaks in LL and 2,459 TSS in LD conditions (Dataset S4).…”
Section: Countmentioning
confidence: 99%
“…S5A) (23). Our initial approach was to assign only the nearest TSS as a target of the peak, but we expanded our analysis to include all TSS within 1 kb of the peak, thus allowing more than one target per peak and the inclusion of bidirectional promoters (51,52). This inclusive target list identified 2,327 TSS within 1 kb of the peaks in LL and 2,459 TSS in LD conditions (Dataset S4).…”
Section: Countmentioning
confidence: 99%
“…Similarly, plant BDPs function in the regulation of important agricultural traits131415161718. The transcription of bidirectional protein-coding gene pairs arranged with in a head-to-head orientation is controlled by bidirectional promoters (BDPs), which have been intensively investigated in eukaryotic genomes, ranging from yeast1920, Drosophila 21, and humans522 to plants2324.…”
mentioning
confidence: 99%
“…These results suggested that Pxy promoter sequence is activated during infection. Bidirectional promoters are known to be regulated in specific tissues at particular developmental stage or triggered during stress of hormonal stimulation 8,44 . www.nature.com/scientificreports www.nature.com/scientificreports/ In synthetic biology and genetic engineering, the strength of the promoter is crucial to drive the expression of the heterologous protein.…”
Section: Discussionmentioning
confidence: 99%